Fundamental relationship between operon organization and gene expression - Lim, Han N. (National Academy of Sciences, 2011)
Half a century has passed since the discovery of operons (groups of genes that are transcribed together as a single mRNA). Despite the importance of operons in bacterial gene networks, the relationship between their organization and gene expression remains poorly understood. Here we show using synthetic operons in Escherichia coli that the expression of a given gene increases with the length of the operon and as its position moves farther from the end of the operon. These findings can be explained by a common mechanism; increasing the distance from the start of a gene to the end of the operon (termed the “transcription distance”) provides more time for translation to occur during transcription, resulting in increased expression. We confirmed experimentally that the increased expression is indeed due to increased translation. Furthermore our analysis indicates the translation initiation rate for an mRNA is sixfold greater during transcription than after its release, which amplifies the impact of the transcription distance on gene expression. As a result of these mechanisms, gene expression increases by ∼40% for each 1,000 nucleotides of transcription distance. In summary, we demonstrate that a fundamental relationship exists between gene expression and the number, length, and order of the genes in an operon. This relationship has important implications for understanding the functional basis of genome organization and practical applications for synthetic biology.